2017
DOI: 10.1371/journal.pone.0170730
|View full text |Cite
|
Sign up to set email alerts
|

Human Empathy, Personality and Experience Affect the Emotion Ratings of Dog and Human Facial Expressions

Abstract: Facial expressions are important for humans in communicating emotions to the conspecifics and enhancing interpersonal understanding. Many muscles producing facial expressions in humans are also found in domestic dogs, but little is known about how humans perceive dog facial expressions, and which psychological factors influence people’s perceptions. Here, we asked 34 observers to rate the valence, arousal, and the six basic emotions (happiness, sadness, surprise, disgust, fear, and anger/aggressiveness) from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 75 publications
(115 reference statements)
5
53
2
Order By: Relevance
“…Our analyses demonstrate that all respondents were highly attached to their companion animals, and the attachment levels positively correlated with the willingness to attribute emotions to companion animals. This finding implies that a combination of animal experience (pet ownership) and strong attachment may promote owners’ brain activations to attributing emotions to animals [ 5 ]. The identification of this correlation could serve as an alternative to or complementary part of existing methods to assess animal emotions, as well as animal welfare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analyses demonstrate that all respondents were highly attached to their companion animals, and the attachment levels positively correlated with the willingness to attribute emotions to companion animals. This finding implies that a combination of animal experience (pet ownership) and strong attachment may promote owners’ brain activations to attributing emotions to animals [ 5 ]. The identification of this correlation could serve as an alternative to or complementary part of existing methods to assess animal emotions, as well as animal welfare.…”
Section: Discussionmentioning
confidence: 99%
“…An important ethical issue in animal welfare appears precisely due to the opinions held by many people that most animals have emotional experiences. If animals experience disappointment and fear due to an inability to perform their natural behavior patterns or, more directly, due to animal cruelty, then this has moral importance and, in turn, may have a major influence on animal welfare [ 4 , 5 ]. Therefore, a better understanding of animal emotions is an important step toward promoting optimum animal welfare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown that human emotions are contagious to dogs [19,20]. Humans in turn are able to attribute emotions to dogs' facial expressions [21] and vocalizations [22].…”
Section: Introductionmentioning
confidence: 99%
“…As amygdala processes both negative and positive emotions 44 , we cannot rule out the effect of arousal in the current emotion-sensitive responses instead of the stimulus valence. Previously, when the current stimuli were www.nature.com/scientificreports/ rated by human subjects, threatening/aggressive dogs received the highest scores for both arousal and negative valence, followed by threatening/angry humans 45 . The early brain responses of dogs in this study follow the same pattern.…”
Section: Threat and Emotional Information Of Facial Expressions In Pmentioning
confidence: 91%